Comparative analysis of developmental and molecular correlates of developmental competence of buffalo oocytes derived from small and large follicles - PANDEY, SRITI; SOMAL, ANJALI; PARMAR, M S; GUPTA, SWATI; CHANDRA, VIKASH; KUMAR, G SAI; SHARMA, G TARU (The Indian Journal of Animal Sciences, 2017)
The present study was conducted to correlate the developmental competence of large follicle (LF, >6 mm) and small follicle (SF,